Split Screen Nation: Vernacular Screen Forms of the American Paradox - Susan Courtney (Revue LISA)
This essay introduces an eclectic history of popular U.S. film, including but well beyond Hollywood cinema, that mediated conflicted sentiments about the U.S. in the decades after the Second World War through an implicit, and sometimes explicit, opposition between the screen South and the screen West. More specifically, the essay detects an interest in this period in mapping the U.S. via moving images and demonstrates that within this phenomenon the South routinely appeared as a kind of moving image problem, and the West as a routine moving image solution for imagining the nation. These dynamics are considered in corporate films promoting car and bus travel, produced for Chevrolet and Greyhound, and in a remarkable amateur film comprised of footage from the 1950s and early 1960s , but not completed until 2000, Robbins Barstow’s Family Camping through Forty-Eight States: Travel Experiences by the Barstow Family of Wethersfield, CT, U.S.A, 1954-1961.